The City and the Village in Toni Morrison’s "Song of Solomon" : reading the space in search for meaning and identity - Teixeira, Susana Vasconcelos (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
.